PELATIHAN DAN PENDAMPINGAN PEMBUATAN ALAT PERAGA EDUKASI DENGAN PRINSIP 4R UNTUK PEMBERDAYAAN GURU RA AT TAQWA SAPEN, MOJOLABAN, SUKOHARJO, JAWA TENGAH: Alat Peraga Edukasi - Rosalina, Neni Nurul; Indarto, Indarto; Budiwiyanto, Joko (Abdi Seni, 2025)
The Art-related Community Service Program at the kindergarten of Raudhatul Athfal At-Taqwa (RA At-Taqwa) aims to foster creativity in artwork creation and improve the skills and competencies of RA teachers in utilizing waste as materials for making Educational Teaching Aids/Games (APE). This approach carries the concept of safety for children, which is environmentally friendly, sourced from materials that are easily obtained from the surrounding environment, with low manufacturing costs, and the application of the 4R principle (Reduce, Reuse, Recycle, Replace). The implementation method includes training, mentoring, and demonstrations to RA At-Taqwa teachers. The implementation strategy goes through Participatory Action Research (PAR) emphasizing empowerment, where teachers are encouraged to increase their creativity in utilizing used materials as an alternative for making APE. This program is also expected to have a positive impact on the school environment by reducing the amount of waste produced and increasing awareness of the importance of maintaining cleanliness and environmental sustainability. The problem faced by partners is the lack of utilization of children's creative potential in the learning process. The limited use of APE has not optimally developed children's creative potential.  This shows that there is still a gap between the potential of children's creativity and the use of available resources in learning. Thus, training and mentoring on the use of used goods is one solution as a means to stimulate and develop children's creativity in the teaching and learning process.